Razvoj znanstvenoraziskovalnega dela študentov MF UM v zadnji 20 letih / The development of the scientific research work of MF UM students in the last 20 years : Uvodni nagovor na kongresu o znanstvenoraziskovalnem delu 17. 5. 2023 na MF UM in UKC Maribor »Od laboratorija do bolnikove postelje« / Introductory speech at the Congress on Scientific Research Work at the MF and the UCC Maribor »From laboratory to hospital bed« - Pahor, Dušica (Acta Medico-Biotechnica, 2023)
The main motto of the University of Maribor is a commitment to research excellence and international comparability in broader research areas, which is also written in the university’s strategy. The Faculty of Medicine is one of the 17 members of the university and, therefore, committed to the fulfilment of all accepted strategic goals and directions for the 2021–2030 period. In order to realize these goals, it is necessary to facilitate optimal research conditions as a precondition for reaching excellence in research. What is particularly important in all of this is connecting scientific research fields among individual faculties within the University of Maribor, as well as in the broader Slovenian area. Especially important is connecting with international research organizations in the context of various projects, engaging in the transfer of science, and making a contribution to the development of society and the progress of a region. Exceptionally important is the integration of students in research work, even at the very beginning of their studies.